SMARTPHONE FOTOGRAFI UNTUK FOTO PRODUK HANDYCRAFT - Siswanta Siswanta (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2021)
This Paper aims to describe the implementation of art and photography skills with smartphone camera devices. The coaching method is done to establish a humanist relationship between coaches and aspiring photographers namely SME entrepreneurs so that there is a sharing experience among the coaching participants so that the participants can produce simple photography but high artistic value. In the early stages of the shooting technique, participants began to understand the difference in the quality of the shooting results of the same object handcraft where the shooting was done with the camera lens of two different smartphones type and the number of camera lenses. The next step, with the direction of coach photographer, the participants have been able to show the creative shooting Handy craft as per the talents of each coaching participant. The implications of this activity are photography techniques using smartphone cameras emphasizing the power aspect of imagination and the creation of human resources rather than the software and hardware aspects used for shooting.